Strategi Pengembangan Agrowisata Ladang Anggrek di Kabupaten Mojokerto, Jawa Timur - Dina Mawarni Pakpahan; Teguh Soedarto; Ida Syamsu Roidah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Agro-tourism is an alternative to sustainable tourism that utilizes agricultural business (agro) as a tourist object, in an effort to develop agro-tourism, the right strategy is needed. This study aims to analyze visitor perceptions and provide development strategies for agro-tourism. The sampling technique was purposive sampling with the criteria and consideration that the party knows the process of developing agro-tourism, as well as other supporting information, the respondents in this study were 96 people. Data analysis was carried out by collecting and compiling data in the form of tabulations. The results of the analysis are then interpreted in a descriptive qualitative manner. The development of agro-tourism is carried out using the SWOT analysis method. Alternative strategies given are increasing HR capabilities, adding facilities and infrastructure that can support the concept of edutourism and involving the government in promoting agro-orchid tourism.